The Endogeneity of Advance Notice and Fear of Destructive Attrition - Fallick, Bruce Chelimsky (The Review of Economics and Statistics, 1994)
This study simultaneously estimates the likelihoods that a worker receives advance notice of a plant closing and that a notified worker quits the job before its scheduled end. The author finds that fear of early attrition is a significant determinant of a firm's decision to provide advance notice. Explicit consideration of employer's concerns may significantly improve prediction of advance notice. Copyright 1994 by MIT Press.